(Not) seeing eye to eye on developmental HRM practices: perceptual (in)congruence and employee outcomes - Marescaux, Elise; De Winne, Sophie (International journal of human resource management, 2024)
This paper focuses on perceptions of Developmental HRM Practices (DHRMP) and their relationship with employee outcomes. We extend the currently existing and predominant social exchange perspective with insights from uncertainty (reduction) theory, to examine vertical (between employee and supervisor) and horizontal (between employee and co-workers reporting to the same supervisor) (in)congruences in DHRMP perceptions, and their relationships with employees' affective organizational commitment (AOC), turnover intention and proactive behavior. Data from 369 employees in 46 teams, and multi-level polynomial regressions show that for vertical (in)congruence, AOC and turnover intention are most favorable when both the employee's and supervisor's perceptions are congruent and positive. This nuances previous research rooted in social exchange theory as it implies that positive employee perceptions of DHRMP, in isolation, are insufficient to maximize both outcomes. In contrast, we find the highest proactive behavior for employees perceiving positive DHRMP, irrespective of their supervisor's perceptions. Finally, for horizontal (in)congruence, AOC and proactive behavior are highest when the employee's perceptions are more positive than their co-workers', and suboptimal when both parties have similarly positive perceptions. This suggests that incongruence in DHRMP perceptions is not necessarily counterproductive.